2005
DOI: 10.1088/0960-1317/15/11/006
|View full text |Cite
|
Sign up to set email alerts
|

Study on anisotropic silicon etching characteristics in various surfactant-added tetramethyl ammonium hydroxide water solutions

Abstract: Three ion-typed surfactants, including anionic sodium dihexyl sulfosuccinate (SDSS), cationic ammonium salt of poly(ethylene glycol) (ASPEG) and non-ionic poly(ethylene glycol) (PEG), were added to 10 wt% tetramethyl ammonium hydroxide water (TMAHW) solutions to evaluate the silicon anisotropic etching properties of the (1 0 0) silicon plane without agitation and no isopropyl alcohol (IPA) additive. The results indicate that the wetting capacity of the etchants cause the efficacies of the etchants on the rough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 32 publications
2
46
0
Order By: Relevance
“…8. The mechanism behind the change in etching characteristics of pure TMAH when a small amount of surfactant is added into it is discussed elsewhere (Merlos et al 1992;Pal et al 2007b;Sundaram et al 2005;Yang et al 2005;Zubel and Kramkowska 2001). The {100} Si substrate is the most widely used in silicon mainstream technology.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…8. The mechanism behind the change in etching characteristics of pure TMAH when a small amount of surfactant is added into it is discussed elsewhere (Merlos et al 1992;Pal et al 2007b;Sundaram et al 2005;Yang et al 2005;Zubel and Kramkowska 2001). The {100} Si substrate is the most widely used in silicon mainstream technology.…”
Section: Resultsmentioning
confidence: 99%
“…TMAH has gained wide popularity due to its clean room compatibility. In the last decade, different kinds of ionic and non-ionic surfactants are studied in TMAH to enhance the applications of wet etching in MEMS (Conway and Cunnane 2002;Jeon et al 1996;Pal et al 2007bPal et al , 2009Resnik et al 2005;Sarro et al 2000;Sekimura 1999;Yang et al 2005). The addition of a very small amount of surfactant in TMAH significantly reduces the etch rate of high index planes, resulting in a reduction of the undercutting at sharp convex, curved and non-h110i edges.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To eliminate the problem of large spatial requirements, more attention must be paid to reduce the undercutting at the convex corners. Several studies for minimizing the undercutting have been reported [28][29][30][31][32][33][34][35][36][37][38]. In case of KOH, IPA is used [28,29], whereas various kinds of surfactants and IPA are reported for TMAH solutions [29][30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…[32,35] Base concentration and additives in -OH based wet etching chemistries influence the quality of the surface morphology. [36,37,38] Optimization of the pre-treatment of the recess surface before SiGe epi processing is also known to be critical to achieve acceptable SiGe morphology and proper surface cleanliness. [35] The doping concentration of the Si to be etched to form the recess also strongly impacts on the etching: During etching, Boron-doped Si forms borosilicate glass on the exposed Si surface, which acts to create etch stop if the boron doping concentration exceeds 10 18 cm -3 .…”
mentioning
confidence: 99%